Imagery, melody and gesture in cross-cultural perspective - Fatone, Gina A.; Clayton, Martin; Leante, Laura; Rahaim, Matt (2011)
Musical action is also physical action. This is obvious in cases such as moving the arm to direct a bow across a cello string, turning the hand to control the vibrations of a drumhead or inclining the cartilages of the larynx to raise the pitch of a sung note. In addition to producing sound, however, physical motion can also serve as a means of conceiving and conveying music: motion is linked in turn to visual imagery and other aspects of the conceptualization of music. Auditory, motor, visual and conceptual counterparts may be integrated, generating a unified meaningful action. In this chapter we present some examples of such crossmodal phenomena in the context of music and gesture: we discuss, for instance, ways in which visual information in the form of gestures contributes to the way musical performance is experienced, and how mental images of spaces, actions and object motion – co-presented in physical gestures – can influence the way music is performed and play an important role in teaching. The chapter, therefore, locates physical gesture within a complex of cross-modal actions associated with musical performance and transmission. We present four approaches to analysing relationships between musical sound and gesture in the performances and teaching of individual musicians. Three of these studies are drawn from the world of North Indian vocal music, the fourth comes from the world of bagpipe music in Atlantic Canada.
EPrint Processing Status: Full text deposited in DRO